Characteristics of Farming Families on Nutrition Choices and Stunting Incidents in Ogan Ilir Regency - Nico Sebayang; Jabal Tarik Ibrahim; Adi Sutanto; Erni Hawayanti; Chuzaimah Chuzaimah; Diah Eka Puspita; Idealistuti Idealistuti; Endang Lastinawati; Harum Sahara (Politeknik Negeri Lampung., 2024)
Government Ogan Ilir Regency is committed to alleviating the stunting problem, especially for most farming families ​ suffering from stunting. The research was conducted on mothers' toddler nutrition not aged 13 to 59 months in the Farming families in nine Posyandu (Integrated Healthcare Posts) in three different sub-districts, based on the Decree of the Regent of Ogan Ilir 2023, Number 188/KEP/DPPPAPPKB/2023 concerning Lokus Village Acceleration Reducing Stunting. The sample used a purposive sampling technique with 17 questions​ grouped into three parts. Data was analyzed using descriptive quantitative and partial least squares (PLS) analysis. The research results show that factor education is the highest for mothers​ influenced by the lack of knowledge about source nutrition for toddlers. The income factor is the highest family​ influenced by the nutrition choices menu when there is money—the priority of using cash in the house and the assumption that work no means wealthy. The schedule influences the highest consumption factor. All variables have convergent validity and are related to mutual relationships. The condition results in a social economy and farming families. The incidence of stunting in Ogan Ilir Regency was 59.8 %, significantly influenced by education and income factors. The effect of the moderation factor education is confirmed to be a significant strengthening factor of income and a factor that affects the consumption of farming families and stunts incidents in Ogan Ilir Regency. Additionally, the effects​ of moderation factor income were confirmed to be very significant, strengthening factor consumption farming families to stunting incidents in Ogan Ilir Regency.